Volumen, tamaño y ajuste a nueva información en el mercado accionario chileno - Marshall, Pablo; Walker, Eduardo (Estudios de Economía, 2016)
This article studies the serial dependence and the speed of adjustment to new information of weekly portfolios returns of stocks traded in the Santiago de Chile stock exchange. Portfolios grouped by size and traded volume during the period 1991-2000 are considered. With the purpose of detecting the predictive power of the lagged returns of certain groups of stocks on others, the study analyzes autocorrelations, crossed-serial correlations, Dimson regressions and vector autoregressions. The evidence indicates that weekly returns are significantly autocorrelated, with a significant crossed-serial effect as well: a 1 percent shock in the returns of the most traded and large (prime) stocks predicts a significant cumulative return between 0,4 and 0,5 percent in the other stocks. There is also evidence of a separate liquidity effect and, in a smaller magnitude, of a size effect, which imply the existence of cross-serial correlation. Above all, however, the joint effect prevails. This evidence supports the hypothesis of a delayed reaction to information of the smaller and less liquid stocks. Given the order of magnitude, the effect could be exploitable.